Lefebvre, love, and struggle : spatial dialectics - Shields, Rob, 1961- (International library of sociology., 1999)
In the only comprehensive guide to Lefebvre's work, Rob Shields draws on the full range of Lefebvre's writings including many previously untranslated and unpublished works and correspondence.